Usefulness of MRI in delineation of dermal and subcutaneous verrucous hemangioma - K Nagarajan; C S Banushree (Wolters Kluwer Medknow Publications, 2015)
Magnetic resonance imaging (MRI) has established itself as diagnostic modality of choice of soft tissue and musculoskeletal lesions but dermatological lesions have been diagnosed mainly by clinical examination. We present MRI features of dermal and subcutaneous verrucous hemangioma involving the dorsum of foot in a 20-year-old male and its usefulness in differentiating it from angiokeratoma with similar clinical features.